The effect of substitution of cottonseed cake by blood meal as source protein in ration for fattening lambs - Ahmed, H.E.; Sulieman, A.H. (1988)
The effects of two rations containing either cottonseed cake or blood meal on the growth performance and carcass characteristics were studied. The experiment involved 24 Shugor male lambs, about four months old, fattened for 63 days. The two rations, iscaloric and isonitrogenous, contained, among other components, either cottonseed cake (A) or blood meal (B). The average liveweight gain and feed conversion efficiency of the lambs were not significantly affected by the source of protein in the offered diets. However, the proportion of the gut fill was significantly (p < 0.05) increased by feeding the blood meal. All carcass pararmeters were not affected by feeding or replacement of cottonsecd cake in the ration.